The Influence Of Training Methods Single Leg Hop And Double Leg Hop Against The Explosive Power Of The Leg Muscles Of PJKR Stkip Yapis Dompu Students - Munandar, Rizky Aris; Hidayat, Taufiq; Pratama, Sandi Achmad (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study uses a "randomized group pretest and posttest design." The population in this study consists of 70 male students from the PJKR Program at STKIP YAPIS DOMPU, class of 2023. The sampling technique used was random sampling with a sample size of 30 people, divided into 3 groups: the Single Leg Hop group, the Double Leg Hop group, and finally, the control group. The type of this research is a quasi-experiment, with a quantitative approach. Data were collected using measurement techniques with the Vertical Jump tool to measure the Explosive Power of the Leg Muscles. Data were analyzed using the MANOVA technique, with an α of 0.05. The research results show that the effect of Single Leg Hop on the improvement of leg muscle explosiveness has a p-value of 0.085, while the effect of Double Leg Hop on the improvement of leg muscle explosiveness has a p-value of 0.030. From both exercises, it turns out that Single Leg Hop is better than Double Leg Hop in improving the explosive power of the leg muscles.This study uses a "randomized group pretest and posttest design." The population in this study consists of 70 male students from the PJKR Program at STKIP YAPIS DOMPU, class of 2023. The sampling technique used was random sampling with a sample size of 30 people, divided into 3 groups: the Single Leg Hop group, the Double Leg Hop group, and finally, the control group. The type of this research is a quasi-experiment, with a quantitative approach. Data were collected using measurement techniques with the Vertical Jump tool to measure the Explosive Power of the Leg Muscles. Data were analyzed using the MANOVA technique, with an α of 0.05. The research results show that the effect of Single Leg Hop on the improvement of leg muscle explosiveness has a p-value of 0.085, while the effect of Double Leg Hop on the improvement of leg muscle explosiveness has a p-value of 0.030. From both exercises, it turns out that Single Leg Hop is better than Double Leg Hop in improving the explosive power of the leg muscles.